Differing hypertrophy patterns from open and closed kinetic chain training affect quadriceps femoris center of mass and moment of inertia - Earp, Jacob E.; Angelino, Domenic; Hatfield, Disa L.; Colantuono, Vincent; Jackson, Euan R.; Morgan, Kristin D.; Adami, Alessandra; Melanson, Kathleen J.; Blazevich, Anthony J. (Frontiers in Physiology, 2023)
PURPOSE: To determine whether kinetic chain pattern during knee extensor strength training influences quadriceps femoris center of mass and moment of inertia about the hip in a predictable manner as such changes can affect running economy. METHODS: Twelve participants completed 8 weeks of both unilateral open (OKC) and closed (CKC) kinetic chain resistance training on opposing legs. Changes in quadriceps femoris muscle volume (VOLQF), center of mass location (CoMQF), and moment of inertia (IQF) about the hip were determined from MRI scans. Regional hemodynamics of the vastus lateralis taken at 30% and 70% of muscle length during OKC and CKC bouts early in the training program were measured using near-infrared spectroscopy (NIRS) and used post-hoc to predict changes in CoMQF. RESULTS: While increases in VOLQF were similar between OKC (Δ79.5±87.9 cm3) and CKC (Δ60.2±110.5 cm3, p=0.29), the patterns of hypertrophy differed; a distal shift in CoMQF (Δ2.4±0.4 cm, p<0.001) and increase in IQF (Δ0.017±0.014 kg∙m2, p<0.001) occurred in OKC but not in CKC (CoMQF: Δ-2.2±2.0 cm, IQF: Δ-0.022±0.020 kg∙m2, p>0.05). Regional hemodynamics assessed by NIRS during a single training session displayed similar exercise and regional differences and predicted 39.6% of observed changes in CoMQF. CONCLUSIONS: Exercise selection influences muscle shape sufficiently to affect CoMQF and IQF, and these changes may be predicted in part from NIRS measurements during a single workout. Given IQF is inversely related to running economy CKC exercise provides a more proximal pattern of hypertrophy than OKC, which may be more preferential for running. The results from the present study also highlight the potential of NIRS as a tool for predicting patterns of hypertrophy between different exercises and exercise conditions.